Broadband nonlinear optical and optical limiting effects of partially unzipped carbon nanotubes. Issue 38 (9th September 2015) - Zhang, Yan; Song, Yingpan; Gan, Yao; Feng, Miao; Zhan, Hongbing
Abstract : Partially unzipped carbon nanotubes can be regarded as CNT–graphene hybrids with a graphene like structure strongly attached to the intact inner walls of the nanotubes. They present a much lower F th than graphene oxide nanosheets and carbon nanotubes at both 532 and 1064 nm, indicating a superior broadband optical limiting effect. Abstract : Many studies have shown that both carbon nanotubes (CNTs) and graphene are important broadband nonlinear optical (NLO) and optical limiting (OL) materials. As hybrids of CNTs and graphene, partially unzipped carbon nanotubes (PUCNTs) can be expected to exhibit superior NLO and OL effects. In this work, PUCNTs were obtained through lengthwise cutting and unraveling of multi-walled carbon nanotubes. The structure and component of PUCNTs were confirmed by transmission electron microscopy, scanning electron microscopy, powder X-ray diffraction, Fourier-transform infrared and Raman spectra. NLO and OL properties were investigated by the Z -scan technique at both 532 and 1064 nm in the nanosecond regime, in comparison with CNTs and graphene. A remarkable enhancement was observed, which can be attributed to the synergistic effect of nonlinear scattering and nonlinear absorption.